2021
DOI: 10.1155/2021/6671814
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MALAT1 Regulates Mouse Granulosa Cell Apoptosis and 17β-Estradiol Synthesis via Regulating miR-205/CREB1 Axis

Abstract: Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), a known long noncoding RNA, was reported to play a crucial role in follicular growth and ovarian disease. However, the physiological function of MALAT1 in mouse granulosa cells (mGCs) remains largely unclear. The aims of this study were to determine the biological function and molecular mechanism of MALAT1 in mGCs. We knocked down MALAT1 in mGCs by using siRNA against MALAT1. We found that knockdown of MALAT1 promoted apoptosis and caspase-3/9 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…PWNR2 plays an important role in oocyte nuclear maturation in PCOS by functioning as a ceRNA to reduce the availability of miR-92b-3p for TMEM120B target binding during oocyte maturation in PCOS ( 62 ). lncRNA MALAT1 regulated apoptosis and estradiol synthesis of mouse GCs through the miR-205/CREB1 axis ( 63 ). The long non-coding RNA Xist regulates oocyte loss via suppressing miR-23b-3p/miR-29a-3p maturation and upregulating STX17 in perinatal mouse ovaries ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…PWNR2 plays an important role in oocyte nuclear maturation in PCOS by functioning as a ceRNA to reduce the availability of miR-92b-3p for TMEM120B target binding during oocyte maturation in PCOS ( 62 ). lncRNA MALAT1 regulated apoptosis and estradiol synthesis of mouse GCs through the miR-205/CREB1 axis ( 63 ). The long non-coding RNA Xist regulates oocyte loss via suppressing miR-23b-3p/miR-29a-3p maturation and upregulating STX17 in perinatal mouse ovaries ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA steroid receptor RNA activator increases cell growth, inhibited apoptosis and induced secretion of E2 and P4 in mGCs ( 29 ). Metastasis-associated lung adenocarcinoma transcript 1 regulates mGC apoptosis and the secretion of E2 and P4 by regulating the miR-205/CREB1 axis ( 30 ). The present study revealed that knockdown of NEAT1 promoted cell proliferation, inhibited apoptosis and induced secretion of E2 and P4 by sponging miR-874-3p, thus suggesting that NEAT1 might be involved in follicular atresia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circLDLR in exosomes serves as a vital mediator to regulate estradiol secretion by sponging miR-1294 to repress the CYP19A1 gene in humans [ 80 ]. LncRNA-MALAT1 regulates the GCs of mouse apoptosis and 17β-estradiol synthesis by regulating the miR-205/CREB1 axis [ 81 ]. CircINHA could resist GCs apoptosis by upregulating CTGF as a ceRNA of miR-10a-5p in pig ovarian follicles [ 24 ].…”
Section: Discussionmentioning
confidence: 99%